2011
DOI: 10.1007/s12015-011-9322-y
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Trial: Undifferentiated Versus Differentiated Autologous Mesenchymal Stem Cells Transplantation in Egyptian Patients with HCV Induced Liver Cirrhosis

Abstract: Bone marrow MSCs transplantation either undifferentiated or differentiated can be used as a potential treatment for liver cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
123
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(131 citation statements)
references
References 31 publications
6
123
0
Order By: Relevance
“…These results agree with different studies suggested a supportive role of undifferentiated WJ-MSCs in rescuing injured liver functions [24]. In addition, WJ-MSCs have properties of anti-inflammatory and antifibrosis by endogenous secreted factors such as metalloproteinase [25].…”
Section: Discussionsupporting
confidence: 92%
“…These results agree with different studies suggested a supportive role of undifferentiated WJ-MSCs in rescuing injured liver functions [24]. In addition, WJ-MSCs have properties of anti-inflammatory and antifibrosis by endogenous secreted factors such as metalloproteinase [25].…”
Section: Discussionsupporting
confidence: 92%
“…In the field of liver cirrhosis, as shown in Table 1, many autologous [70][71][72][73][74][75][76][77][78][79][80][81][82][83] and four allogeneic [59][60][61][62] MSC therapies involving a variety of tissue origins and administration routes have been reported. Although details regarding the mechanisms of therapeutic effects in humans remain unclear, most studies have reported favorable effects with improvement in MELD scores, Child-Pugh scores, and some serum markers such as albumin and bilirubin.…”
Section: Mscsmentioning
confidence: 99%
“…A subsequent study in 2012 assessed the potential effects of hepatocyte-like cells differentiated from BMMSCs prior to infusion as compared to undifferentiated BM-MSCs in 25 liver cirrhosis patients [55]. While this study showed that the intravenous infusion of 1 × 10 6 cells per kg body weight is safe and improves liver function, the clinical outcomes between both treatment groups did not vary.…”
Section: Allogeneic Stem Cells In Liver Cirrhosis Therapymentioning
confidence: 93%